Photodynamic therapy using 5-aminolaevulinic acid for experimental pancreatic cancer--prolonged animal survival. - Regula, J. (Nature Publishing Group, 1994)
Experimental studies have been carried out using 5-aminolaevulinic acid (ALA) to induce transient porphyrin photosensitisation for photodynamic therapy (PDT) in a pancreatic cancer model in Syrian golden hamsters. ALA was given either intravenously or orally (in bolus or fractionated doses) with the laser light delivered by means of a bare fibre touching the tissue surface or external irradiation using a light-integrating cylindrical applicator. Animals were killed 1-24 h after ALA administration for pharmacokinetic studies and 3-7 days after light exposure to study PDT-induced necrosis. A separate survival study was also performed after a fractionated oral dose of ALA and external irradiation. Protoporphyrin IX sensitisation in the tumour tissue as measured by quantitative fluorescence microscopy was highest after intravenous administration of 200 mg kg-1 ALA and then in decreasing order after oral fractionated and oral bolus doses (both 400 mg kg-1). Laser light application at 630 nm to give 12-50 J from the bare fibre or 50 J cm-2 using surface illumination with the cylindrical applicator resulted in tumour necrosis up to 8 mm in depth. In larger tumours a rim of viable tumour was observed on the side opposite to illumination. In a randomised study, survival of treated animals was significantly longer than in the untreated control group (log-rank test, P < 0.02), although all animals died of recurrent tumour. This technique shows promise in the treatment of small volumes of tumour in the pancreas. IMAGES: